The co-production of hydrogen and methane from dark fermentation of mixed palm oil mill effluent and aquaculture wastewater : Gompertz modelling and sludge recovery - Siddique, Md. Nurul Islam; Aina, Kamil; Mohd Zamri, Ibrahim; Noraaini, Ali; Nazaitulshila, Rasit; Shahrul, Ismail; Zaied, Khalid; Wan Sani, Wan Nik (Asian Publication Corporation, 2023)
The potentials for non-stop hydrogen and methane production employing an ideal loading mixture of palm oil mill effluent (POME) and aquaculture wastewater (AWW) in a double-phase digester at a thermophilic state are presented. Different organic loadings were studied such as 31, 41, 51 and 61 Kg COD/(m3d) for the generation of hydrogen; 9, 11, 14 and 16 kg COD/(m3d) for the synthesis of methane. In a UASB reactor, hydrogen production was kept under control with a constant HRT of 12 h. At the loading of 51 kg COD/h, the maximal H2content, volumetric H2generation rate and H2yield were observed as 46%, 6 L H2/d and 34 mL H2/g COD, respectively (m3d). After an HRT of 6 days, the substrate from the hydrogen digester was further fermented into methane in the CSTR digester. At an organic loading rate of 14 kg COD/h, the highest volumetric CH4generation rate and yield were 11 L CH4/d and 0.13 m3CH4/kg COD, respectively (m3d). This two-stage procedure removed 92% of the chemical oxygen requirement overall. Based on the findings, the Gompertz modeling was a good fit for the cumulative methane generation patterns, with a strong correlation coefficient (> 0.994). Sludge recovery was 0.07 m3sludge/m3wastewater and water recovery was 0.82 m3/m3wastewater. This double-phase technique has the potential to contribute greatly to the development of a comprehensive waste management plan, including the digestion of palm oil mill effluent and aquaculture wastewater.